2017
DOI: 10.1016/j.biopsych.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical Mediation of Affiliation and Aggression Associated With Pair-Bonding

Abstract: Background The neuropeptides vasopressin (AVP) and corticotrophin-releasing hormone (CRH) facilitate while serotonin (5-HT) inhibits aggression. How the brain is wired to coordinate interactions between these functionally opposed neurotransmitters to control behavioral states is poorly understood. Methods Pair-bonded male prairie voles (Microtus ochrogaster) were infused with a retrograde tracer, fluorogold, and tested for affiliation and aggression toward a female partner or novel female. Subsequent immunoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 91 publications
2
31
0
Order By: Relevance
“…Together with these reports, our results imply the involvement of a serotonin system in the formation of pair bond in prairie voles. This idea is consistent with a very recent report indicating that a subset of inhibitory serotonergic neurons projecting to the anterior hypothalamus mediate spatiotemporal release of neuropeptides in modulating affiliation [51]. …”
Section: Discussionsupporting
confidence: 93%
“…Together with these reports, our results imply the involvement of a serotonin system in the formation of pair bond in prairie voles. This idea is consistent with a very recent report indicating that a subset of inhibitory serotonergic neurons projecting to the anterior hypothalamus mediate spatiotemporal release of neuropeptides in modulating affiliation [51]. …”
Section: Discussionsupporting
confidence: 93%
“…Remarkably, most of the former are well‐known key players of the reward system, such as dopamine, noradrenaline, cannabinoids, oxytocin or opioids (Dolen et al , ; Coria‐Avila et al , ; Baribeau and Anagnostou, ; Loureiro et al , ; Vanderschuren et al , ), and have been initially identified as neurochemical mediators of the motivational/rewarding properties of drugs of abuse and/or as pain killers. In contrast, neurobiological substrates of social avoidance [social avoidance systems (SAS)] have been characterized as main factors of the pain, aggression or stress systems and include 5‐HT, glucocorticoids and neuropeptides such as corticotropin‐releasing factor, arginine vasopressin, substance P or cholecystokinin (Katsouni et al , ; Takahashi et al , ; Barik et al , ; Katsouni et al , ; Gobbroge et al , ). Pro‐social and anti‐social neuromodulators thus compete to drive adaptive social behaviour in individuals.…”
Section: Social Reward and Social Pain: Overlapping Neurobiological Smentioning
confidence: 99%
“…Novel semi-naturalistic field studies in prairie voles has found that DNA variation in the V1aR gene includes polymorphisms that predict the epigenetic status and neuronal expression of V1aR in a spatial memory circuit and this genomic diversity in V1aR is favored by selection [59 •• ] . Finally, our most recent data reveal neurochemical interactions between AVP, serotonin (5-HT), and CRH, in a neuronal microcircuit, encoding a male prairie vole’s decision to affiliate or fight his female partner or a stranger female [60 •• ] . Together with previous studies, the prairie vole field is ripe for incorporating contemporary molecular genetic tools like genomic tract-tracing, opto/chemo-genetic approaches, and gene editing via CRISPR technology.…”
Section: Discussionmentioning
confidence: 99%